Nursing of COVID-19 patients in the mobile cabin hospital (方舱医院内新型冠状病毒感染患者的护理体会) - ZHANG Xiuying (张秀颖); LI Dongran (李东冉); ZHU Chunzi (竺春子); ZHANG Yuan (张媛) (中西医结合护理)
This paper summarized the nursing management for COVID-19 patients in the mobile cabin hospital. Targeted nursing plan was established based on comprehensive analysis of clinical symptoms. Enhanced health education was carried out to regulate patients’ mental status and improve the treatment complication (本文总结方舱医院内新型冠状病毒感染患者的护理体会。从新型冠状病毒感染患者症状入手, 采取相应的护理措施, 同时加强健康教育, 调整患者心理状态, 提高治疗依从性。)